Dampak Transformasi Teknologi pada Sistem Perpajakan dan Stabilitas Pendapatan Pajak di Semarang - Niamy, Faiz Mazda (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This study aims to determine the impact of technological transformation on the tax system and tax revenue stability in Semarang, with a focus on case studies in the Semarang area. With the phenomenon of technological advances that are increasingly advanced today, of course it has an impact on the tax system, therefore this research wants to examine what impact is caused by this phenomenon. The research method used is to use a mixed methods approach. This research design is descriptive, which allows researchers to describe the phenomena that occur in the tax system and explore the factors that affect tax stability. The research population consists of taxpayers registered in Semarang and tax officers working in local taxation agencies. The results showed that technological transformation in the taxation system is very helpful and easy and makes taxation itself which was originally before the transformation of technology is very complicated to be simpler, with this convenience also has an impact on the stability of tax revenue in Semarang because the access provided becomes easier and more flexible.